Implementation of Project Based Learning to Improve Understanding of the Concept of Rights and Obligations in Grade IV Students of SDN Cihajere - Rina Lisyana; Ageng Triyono (Civiliza Publishing, Indonesia., 2026)
This study aims to describe the implementation of the Project Based Learning (PjBL) model through poster-making projects in Civic Education (PPKn) and to analyze its effect on enhancing the understanding of rights and obligations among fourth-grade students at SDN Cihajere. The research employed Classroom Action Research (CAR) using the Kemmis & McTaggart model, conducted in two cycles and involving 40 students. Each cycle comprised the stages of planning, action, observation, and reflection. Data were collected through concept understanding tests and observation sheets on the implementation of learning activities. The results showed a significant increase in the average test scores, from 58 (pre-cycle) to 68 (cycle I) and 82 (cycle II). The percentage of classical mastery rose from 35% to 60%, and finally to 88%. Moreover, the application of PjBL encouraged active student participation in group discussions, improved argumentative and collaborative skills, and stimulated creativity through the production of educational posters. These findings indicate that PjBL is effective in improving students’ understanding of the concepts of rights and obligations. This study recommends the integration of poster-based PjBL as an innovative strategy in Civic Education to strengthen the understanding of rights and obligations at the elementary school level.